Communication Skills and Their Socio-Sexual Predictors After Husbands’ Retirement: Gender Differences - Somayeh Azimi; Zeinab Javadivala; Mina Izadi; Neda Ghilani; Hamid Allahverdipour (SAGE Open)
People’s retirement usually happens in their old age; therefore, the lack of communication skills (CS) and conflict between couples make the elderly face many challenges that can affect their marital relationships. The objectives of this research were to investigate the relationship between demographic and sexual variables with communication skills and the role of communication skills in predicting social and sexual factors in the retired elderly. This descriptive-analytical study was carried out on 156 couples referred to the urban health centers in Tabriz, Iran from January to Jul 2021. Inclusion criteria were retired men over 60 years old with a history of retirement of about >6 months and not working part-time or full-time elsewhere. Sexual characteristics including marital satisfaction, initiator of sexual behavior, arousal/Erection problem, verbal interaction, going, and going to bed together, were predictors of CS only among husbands ( p  < .05). But intercourse desire was a predictor of CS only in women so more desired women had 1.95 units more CS than women who were not desired ( p  < .05). This study found that despite the relationship between sexual characteristics and CS, the predictors of CS are different between wives and husbands. So CS training could be useful in enhancing the marital relationship of elderly couples. Policymakers can use this information to help retired couples through retirement planning and transitions.